Defining Older People in Chile: Challenges in Planning Policies for Ageing Populations - Villalobos-Dintrans, P (Oxford University Press, 2020)
The concept of older adult is extensively used in day-To-day discussions and public policy. Nonetheless, concrete operational definitions are scarce. This poses a challenge for policymakers when designing initiatives targeted to this population. Chronological age has been traditionally used as the sole criteria for identifying older people (OP). However, there is no consensus about what is the age that should define an elderly. The issue became evident when, in 2018, the Chilean Ministry of Health started a planning process to coordinate health initiatives for OP. Two thresholds had been commonly used-60 and 65 years-and the differences between choosing one and the other were significant. This article intends to structure the debate around age thresholds and the definition of OP in Chile, presenting information and evidence to guide decision-makers when deciding about the issue. Information was based on international guidelines and definitions, laws and practice in the country and epidemiological data. The analysis shows a lack of consensus when dealing with the definition of OP using age thresholds at every level. Results highlight the difficulty of using age as a guide for designing policies for OP and call for a more holistic way for identifying OP as beneficiaries of targeted programmes, considering the heterogeneity of this population and the availability of information. This debate is much needed in many countries that, like Chile, will experience significant demographic changes and face the challenges of healthy ageing. © 2020 The Author(s) 2020. Published by Oxford University Press in association with The London School of Hygiene and Tropical Medicine. All rights reserved. For permissions, please e-mail: journals.permissions@oup.com.